Hubungan Faktor Petugas Puskesmas dengan Cakupan Penderita Tuberculosis Paru BTA Positif - Efrizon Hariadi, Iswanto, Riris Andono Ahmad (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Tuberculosis (TB) disease is a major health problem either in developed or developing countries. According to WHO TB happens to 25,205 people worldwide everyday, ending in mortality to 4,657 people. Indonesia is in the third rank of TB cases in the world after India and China. TB in Indonesia happens to 1,464 people everyday, ending in mortality to 241 people. The identification of suspect and positive acid fast bacillus is a performance indicator of lung TB program. At District of Bengkulu 2007 lung TB patients’ identification was still below the national target, i.e. 38.193. The screening and identification of patients is generally done by nurses at polyclinics and laboratory staff. Nurses are health professionals at the front liners of health services with quite large composition (40%).Objective: To identify factors of the health center in relation to the coverage of positive acid fast bacillus lung TB patients at District of Bengkulu Utara.Method: This was an observational study with a cross sectional design. Location of the study was microscopic referral health centers, independently managed health centers, and satellite health centers at District of Bengkulu Utara. Samples consisted of staff of polyclinic and laboratories. Data were obtained through questionnaire and observation and presented using frequency distribution tables and multilevel regression and linear regression methods.Result: The result of multivariate analysis showed that variables related to the coverage of lung TB patients were skills of staff with b=1.3 (p=0.000) and facilities with b=1.5 (p=0.000).Conclusion: Skills of staff, training of staff, and availability of facilities were related to the coverage of positive acid fast bacillus lung TB patients at District of Bengkulu Utara; therefore it was necessary to improve skills of staff through on the job training and improve facilities for the identification of lung TB patients.Keywords: lung TB, nurses, laboratory staff, TB patient identification